Oviductal response to gametes and early embryos in mammals. Issue 4 (October 2016) - Maillo, Veronica; Sánchez-Calabuig, Maria Jesus; Lopera-Vasquez, Ricaurte; Hamdi, Meriem; Gutierrez-Adan, Alfonso; Lonergan, Patrick; Rizos, Dimitrios
Abstract : The oviduct is a complex and organized thin tubular structure connecting the ovary with the uterus. It is the site of final sperm capacitation, oocyte fertilization and, in most species, the first 3–4days of early embryo development. The oviductal epithelium is made up of ciliary and secretory cells responsible for the secretion of proteins and other factors which contribute to the formation of the oviductal fluid. Despite significant research, most of the pathways and oviductal factors implicated in the crosstalk between gametes/early embryo and the oviduct remain unknown. Therefore, studying the oviductal environment is crucial to improve our understanding of the regulatory mechanisms controlling fertilization and embryo development. In vitro systems are a valuable tool to study in vivo pathways and mechanisms, particularly those in the oviducts which in livestock species are challenging to access. In studies of gamete and embryo interaction with the reproductive tract, oviductal epithelial cells, oviductal fluid and microvesicles co-cultured with gametes/embryos represent the most appropriate in vitro models to mimic the physiological conditions in vivo .